IncSPADE: An Incremental Sequential Pattern Mining Algorithm Based on SPADE Property - Omer, Adam; Zailani, Abdullah; Amir, Ngah; Kasypi, Mokhtar; Wan Muhamad Amir, Wan Ahmad; Herawan, Tutut; Noraziah, Ahmad; Mustafa, Mat Deris; Abdul Razak, Hamdan (Springer International Publishing, 2016)
In this paper we propose Incremental Sequential PAttern Discovery using Equivalence classes (IncSPADE) algorithm to mine the dynamic database without the requirement of re-scanning the database again. In order to evaluate this algorithm, we conducted the experiments against three different artificial datasets. The result shows that IncSPADE outperformed the benchmarked algorithm called SPADE up to 20%.